2023
DOI: 10.1021/acsami.3c04799
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Flame-Resistant, and Anisotropic Thermally Conductive Aerogel Films with Ionic Liquid Crystal-Armored Boron Nitride

Abstract: With the rapid development of miniaturization and high-power portable electronics, the accumulation of undesired heat can degrade the performance of electronic devices and even cause fires. Therefore, multifunctional thermal interface materials that combine high thermal conductivity and flame retardancy remain a challenge. Herein, an ILC (ionic liquids crystal)-armored boron nitride nanosheet (BNNS) with flame retardant functional groups was first developed. The high in-plane orientation structure aerogel film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For PVA, the bands at 3282 and 1091 cm –1 correspond to the −OH stretching vibration and the C–O stretching vibration, respectively. Red shifts in υ O–H and υ C–O were observed in the composite hydrogel after the addition of ANF and TA, which is attributed to the newly formed hydrogen bonds between the molecules reducing the forces between the chemical bonds and causing them to move to lower wavenumbers (Figure a,c) . The O–H peak of the PVA–ANF–FG T composite hydrogel was shifted to 3264 cm –1 , confirming the C–F···H–O hydrogen bonding interaction between the FG nanosheets and PVA .…”
Section: Resultsmentioning
confidence: 76%
“…For PVA, the bands at 3282 and 1091 cm –1 correspond to the −OH stretching vibration and the C–O stretching vibration, respectively. Red shifts in υ O–H and υ C–O were observed in the composite hydrogel after the addition of ANF and TA, which is attributed to the newly formed hydrogen bonds between the molecules reducing the forces between the chemical bonds and causing them to move to lower wavenumbers (Figure a,c) . The O–H peak of the PVA–ANF–FG T composite hydrogel was shifted to 3264 cm –1 , confirming the C–F···H–O hydrogen bonding interaction between the FG nanosheets and PVA .…”
Section: Resultsmentioning
confidence: 76%
“…In addition, BF exhibits high strength, excellent thermal stability, and chemical stability. , Therefore, the production of inorganic paper using BFs holds a promising application in the fields of fire retardance and thermal insulation. However, as a result of its chemical inertness, it is necessary to introduce reinforcing phases in the BF network to improve paper-forming properties and provide more possibilities for the application of BFs in the field of paper-based materials. Aramid fiber is a high-performance organic synthetic fiber with lightweightness, good thermal stability, chemical resistance, insulation, and self-extinguishing properties. Aramid nanofibers (ANFs) retain these excellent properties of macroscopic aramid fibers . Previous studies have shown that ANFs can be used to prepare materials with excellent thermal stability and insulation through processes such as electrospinning, vacuum-assisted pumping filtration, and freeze drying. In addition, ANFs also own the characteristics of nanomaterials, such as high specific surface area and high aspect ratio, which help to improve the interfacial bonding with the substrate, thus enhancing the mechanical properties of the material. , ANFs can serve as reinforcing phases in composites with other matrices, such as bacterial cellulose, poly­(vinyl alcohol), hydroxyethyl cellulose, and carbon nanotubes, improving interface bonding and resulting in a significant enhancement of mechanical strength. Therefore, ANFs show great applications in various high-performance and multifunctional materials.…”
Section: Introductionmentioning
confidence: 99%
“…As porous materials, aerogels have high porosity and surface area, low density, and thermal conductivity. These characteristics lead to their widespread use in catalyst carriers, sensors, absorbers, and aerospace materials. Aerogels derived from polymer materials exhibit excellent mechanical properties, thermal insulation properties, and environmental stability, allowing for their use in temperature sensing and fire safety. If the aerogel is endowed with luminescence properties, the aerogel will have unique optical self-monitoring and tracer functions. , Considering the unique advantage that room-temperature phosphorescent (RTP) materials can continue to glow after the excitation light stops, their introduction into the aerogel system will not only provide a new research direction for the construction of aerogels with optical detection and tracer function but also effectively expand the macroscopic morphology and application range of RTP materials. However, this concept is rarely reported, so the development of RTP polymer aerogels is desired.…”
Section: Introductionmentioning
confidence: 99%